2006
DOI: 10.1086/500651
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Aggressive Infection Control Strategy on Endemic Staphylococcus aureus Infection in Liver Transplant Recipients

Abstract: Use of active surveillance cultures to detect colonization and implementation of targeted infection control interventions proved to be effective in curtailing new acquisition of S. aureus colonization and in decreasing the rate of S. aureus infection that was endemic in our population of liver transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 19 publications
1
51
1
2
Order By: Relevance
“…17,18 Our most notable findings concerned the outcomes of these infections. Contrary to prior reports of high mortality rates among solid organ transplant recipients with staphylococcal infections, 15,19 we found that the 30-and 90-day mortality rates were only 7% and 12%, respectively. However, lung transplant recipients with early-onset S aureus infections were significantly more likely to die at 3 years and have ACR or chronic rejection than those without such infections.…”
Section: Discussioncontrasting
confidence: 99%
“…17,18 Our most notable findings concerned the outcomes of these infections. Contrary to prior reports of high mortality rates among solid organ transplant recipients with staphylococcal infections, 15,19 we found that the 30-and 90-day mortality rates were only 7% and 12%, respectively. However, lung transplant recipients with early-onset S aureus infections were significantly more likely to die at 3 years and have ACR or chronic rejection than those without such infections.…”
Section: Discussioncontrasting
confidence: 99%
“…The pooled effects and sensitivity analyses are displayed in Table 2. Before transplantation, the estimated MRSA colonization was 8.5% (95% CI 3.2-15.8; effect derived from nine studies (13)(14)(15)19,(21)(22)(23)29,33) in 2885 patients (t 2 ¼ 0.107) and VRE colonization was 11.9% (95% CI 6.8-18.2; effect derived from eight studies (14,17,18,20,24,25,35,36) that included 1381 patients (t 2 ¼ 0.060). Effects referred to liver patients exclusively for VRE, whereas for MRSA two out of nine eligible studies reported data on kidney and/or pancreas and lung patients (13,33).…”
Section: Resultsmentioning
confidence: 99%
“…In the postoperative screening, the estimated MRSA colonization was derived from six studies (12)(13)(14)(15)21,32) with 2342 patients (three on liver transplant recipients, one on lung recipients, one on kidney and one on kidney and/or pancreas) and it was 9.4% (95% CI 3.0-18.5; t 2 ¼ 0.096) and across eight VRE studies (14,(16)(17)(18)20,27,30,36) with 1369 patients (six on liver transplant recipients, one on kidney and one on kidney and/or pancreas), colonization was 16.2% (95% CI 10.7-22.6); t 2 ¼ 0.051. There was no evidence of publication bias for MRSA (Egger's bias ¼ 7.15, p ¼ 0.16), or VRE (Egger's bias ¼ 1.12, p ¼ 0.76).…”
Section: Resultsmentioning
confidence: 99%
“…This can be due to many factors: (1) the lower incidence of polymicrobial infections in our study, considering that Wagener et al 31 reported polymicrobial infection was associated with increased mortality after solid organ transplantation; and (2) the lower incidence of invasive fungemia and pneumocystic diseases due to the use of prophylactic antifungal drugs and antibiotics, which proved to minimize the incidence of, and thus mortality from, infection. 30,32,33 For the duration of the study period, the number of deaths due to infection decreased in era 2 compared to era 1; moreover, the pattern of some infection changed between era 1 and era 2 with higher incidence of MRSA in the older era. This may be attributed to the consultation with infectious disease physicians in the treatment decisions that emphasize adequate treatment, which help to improve outcome of MRSA infection and decrease the incidence of deaths due to infection.…”
Section: Discussionmentioning
confidence: 99%